Effects of substrate stiffness and actin velocity on in silico fibronectin fibril morphometry and mechanics. - Seth H Weinberg; Navpreet Saini; Christopher A Lemmon (PLoS ONE)
Assembly of the extracellular matrix protein fibronectin (FN) into insoluble, viscoelastic fibrils is a critical step during embryonic development and wound healing; misregulation of FN fibril assembly has been implicated in many diseases, including fibrotic diseases and cancer. We have previously developed a computational model of FN fibril assembly that recapitulates the morphometry and mechanics of cell-derived FN fibrils. Here we use this model to probe two important questions: how is FN fibril formation affected by the contractile phenotype of the cell, and how is FN fibril formation affected by the stiffness of the surrounding tissue? We show that FN fibril formation depends strongly on the contractile phenotype of the cell, but only weakly on in vitro substrate stiffness, which is an analog for in vivo tissue stiffness. These results are consistent with previous experimental data and provide a better insight into conditions that promote FN fibril assembly. We have also investigated two distinct phenotypes of FN fibrils that we have previously identified; we show that the ratio of the two phenotypes depends on both substrate stiffness and contractile phenotype, with intermediate contractility and high substrate stiffness creating an optimal condition for stably stretched fibrils. Finally, we have investigated how re-stretch of a fibril affects cellular response. We probed how the contractile phenotype of the re-stretching cell affects the mechanics of the fibril; results indicate that the number of myosin motors only weakly affects the cellular response, but increasing actin velocity results in a decrease in the apparent stiffness of the fibril and a decrease in the stably-applied force to the fibril. Taken together, these results give novel insights into the combinatorial effects of substrate stiffness and cell contractility on FN fibril assembly.